Localization of Somatic Antigen on Gram-Negative Bacteria by Electron Microscopy - Shands, J. W. (1965)
Shands, J. W. (University of Florida, Gainesville). Localization of somatic antigen on gram-negative bacteria by electron microscopy. J. Bacteriol. 90:266–270. 1965.—Antisera specific for the somatic antigens of Salmonella typhimurium and Escherichia coli O113 were prepared, and globulins isolated from these antisera were labeled with ferritin. Micrographs of labeled, sectioned bacteria show that somatic antigen is located in considerable quantities on the surface of the bacteria, and, furthermore, that it can extend up to 150 mμ beyond the confines of the cell wall. The arrangement of the ferritin on the bacteria suggests that the antigenic sites are located on fibrillar structures.